PENGARUH CURRENT RATIO, RETURN ON EQUITY, DAN DEBT TO EQUITY RATIO TERHADAP NET PROFIT MARGIN PADA INDUSTRI TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018 – 2022 - Khairunnisa Khairunnisa; Akhmad Julian Saputra; Dewi Setiawati (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
This study aims to test: analyze the effect of Current Ratio, Return On Equity, Debt to Equity Ratio on Net Profit Margin in the Transportation Industry Listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 Period. The population of the study consists of 16 companies in the transportation industry listed on the IDX during the same period. The results of this study indicate that Current Ratio and Return On Equity have a significant partial effect on the Net Profit Margin variable, while Debt to Equity Ratio has no effect on Net Profit Margin.